Exergetic analysis of a continuous plant for the hydrothermal reduction of CO2 into formate - Laura Quintana-Gómez; José J. Segovia; Ángel Martín; M. Dolores Bermejo (Energy Reports, 2022)
Carbon capture and utilization can mitigate the problems caused by CO2 emissions, at the same time that valuable products are obtained from the conversion of CO2. By reduction of CO2 in hydrothermal conditions (T = 275°C, P = 200 bar), high yields of conversion of CO2 to formate of up to 70% can be achieved in reaction times of 1 h. This technology can be implemented as a continuous process in large CO2 production sites, and for this purpose the energy optimization of the process is essential to make it technically and economically feasible. Therefore, the objective of this work is to evaluate the thermodynamic efficiency and the cost of the different units involved in the hydrothermal conversion of CO2 into formate. Exergy balances were applied to the main units of a continuous plant for the hydrothermal reduction of CO2 into formate. The exergy efficiency, exergy improvement potential rate, the exergoeconomic costs and the sustainability index were calculated along with the exergy destruction rate in the main process units. The specific exergy destroyed per kg of formate produced was calculated as 6260 kJ/kg. The results showed that the major exergy destruction rate took place in the reactor, representing the 69% of the total exergy destruction in the plant. Although this destruction rate increased with the conversion in the reactor, in terms of the overall efficiency and exergetic cost of the process, a high conversion above 70% is advisable. The exergetic efficiency of each unit was also evaluated along with the exergetic improvement potential rate. The lowest efficiency was identified in the pump with a value of 0.44. In the case of the exergoeconomic performance, the reactor showed the highest cost rate representing the 67% of the total costs. The total exergoeconomic cost rate was 2.3 €/kg of formate produced.